2001
DOI: 10.1159/000064198
|View full text |Cite
|
Sign up to set email alerts
|

Counselling following the Prenatal Diagnosis of Klinefelter Syndrome: Comparisons between Geneticists and Obstetricians in Five European Countries

Abstract: Objective: To describe and compare the information obstetricians and geneticists in five European countries report they would give following the prenatal diagnosis of Klinefelter syndrome. Methods: 388 obstetricians and 269 geneticists from Germany, the Netherlands, Portugal, Spain and the UK completed a brief questionnaire assessing two variables: the information they reported providing to parents following the prenatal diagnosis of Klinefelter syndrome (categorized as positive or negative); and their percept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 18 publications
0
16
0
Order By: Relevance
“…Other studies have shown that the decision to terminate was made more often when the postdiagnosis counseling was given by an obstetrician compared with a medical geneticist; 14,18,25 the obstetricians were more likely than geneticists to provide more negative information about the condition of 1 specific type of sex chromosome aneuploidy. 18 In our study, we were unable to examine the influence of this factor, because all the couples were counseled by obstetricians with a subspecialty in medical genetics. In Hungary, the vast majority of health professionals who perform prenatal invasive procedures and conduct genetic counseling are obstetricians.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Other studies have shown that the decision to terminate was made more often when the postdiagnosis counseling was given by an obstetrician compared with a medical geneticist; 14,18,25 the obstetricians were more likely than geneticists to provide more negative information about the condition of 1 specific type of sex chromosome aneuploidy. 18 In our study, we were unable to examine the influence of this factor, because all the couples were counseled by obstetricians with a subspecialty in medical genetics. In Hungary, the vast majority of health professionals who perform prenatal invasive procedures and conduct genetic counseling are obstetricians.…”
Section: Discussionmentioning
confidence: 95%
“…4 Our sample size may not reveal small differences between groups; however, it is suggested that the cultural differences in the perceptions of parents and health care professionals regarding quality of life with this condition may mask influences of these factors and may also be the most likely explanation of the various termination rates between centers. 18 The professional identity of the information provider is another factor which may influence the parental decision making in prenatal diagnosis of sex chromosome aneuploidy. Other studies have shown that the decision to terminate was made more often when the postdiagnosis counseling was given by an obstetrician compared with a medical geneticist; 14,18,25 the obstetricians were more likely than geneticists to provide more negative information about the condition of 1 specific type of sex chromosome aneuploidy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been shown that the parents' decision to terminate the pregnancy is influenced by the health professional providing the counseling. The affected pregnancy was more likely to continue if the counseling was given by a genetic specialist (21,22).…”
Section: Prenatal Diagnosismentioning
confidence: 99%
“…Second, the outcomes of pregnancies diagnosed with XXY appear to be influenced by the specialty of the clinician providing the counseling (Marteau et al 2002). Those parents receiving post-diagnosis counseling from a genetics professional are more likely to receive positive information about the condition (Bourke et al 2014; Hall et al 2001) and are also more likely to continue their pregnancy (relative risk: 2.42) (Marteau et al 2002). …”
Section: Introductionmentioning
confidence: 99%